Analisa Spasial Pengaruh Keberadaan Minimarket Waralaba Terhadap Omzet Toko Kelontong di Kecamatan Umbulharjo Kota Yogyakarta - Ilmawan, Kurnia Fahmy, Drs. Priyono, M.Si, Dr. Muhammad Musiyam, M.T.P (2015)
This research aim to analyze spatial aspect of distribution and to verify variable that have effect to income change of traditional stores in Umbulharjo sub district, City of Yogyakarta. Method to analyze data's which had collected using quitionares and to prove research hypothesis is quantitative approach and spatial approach to analyze distribution of traditional store. Refer to spatial analyze method, result of this reseach is spatial pattern of traditional market was clustered with number of Zscore's -7,85579 and there is positive spatial autocorrelation because the number of Morran index is bigger than 0,028 . Density of traditional market in Umbulharjo sub District are concentrated in Warungboto and Pandeyan. Depend on statistics data analyze, comprehensive correlation between independent variables to dependen variable is 40,8 % and there is no linear relation between them. In particular correlations, only distance which have signifianct correlation to income change in 65,2 % than others independent variables.